Azospirillum brasilense promotes increases in growth and nitrogen use efficiency of maize genotypes - Zeffa, Douglas Mariani; Perini, Luiz Júnior; Silva, Mayara Barbosa; de Sousa, Nicholas Vieira; Scapim, Carlos Alberto; Oliveira, André Luiz Martinez de; Amaral Júnior, Antônio Teixeira do; Azeredo Gonçalves, Leandro Simões (PloS one, 2019)
The development of cultivars with an improved nitrogen use efficiency (NUE) together with the application of plant growth-promoting bacteria is considered one of the main strategies for reduction of fertilizers use. In this sense, this study: i) evaluated the effect of Azospirillum brasilense on the initial development of maize genotypes; ii) investigated the influence of A. brasilense inoculation on NUE under nitrogen deficit; and iii) sought for more NUE genotypes with higher responsiveness to A. brasilense inoculation. Twenty-seven maize genotypes were evaluated in three independent experiments. The first evaluated the initial development of maize genotypes with and without A. brasilense (strain Ab-V5) inoculation of seeds on germination paper in a growth chamber. The second and third experiments were carried out in a greenhouse using Leonard pots and pots with substrate, respectively, and the genotypes were evaluated at high nitrogen, low nitrogen and low nitrogen plus A. brasilense Ab-V5 inoculation. The inoculation of seeds with A. brasilense Ab-V5 intensified plant growth, improved biochemical traits and raised NUE under nitrogen deficit. The inoculation of seeds with A. brasilense can be considered an economically viable and environmentally sustainable strategy for maize cultivation.